Dynamic economic resilience scenarios for measuring long-term community housing recovery. (8th August 2022) - Zavareh, Sahar; Winder, Gordon M.
ABSTRACT: The research measures post-disaster long-term housing recovery to assess community resilient recovery using the case of Broadmoor, a community located in New Orleans. Dynamic economic resilience scenarios calculate post-disaster housing recovery and differences of rebuilding using three housing recovery scenarios (baseline, reference recovery and dynamic economic resilience). The baseline scenario projects changes in housing market values without a disaster. The reference recovery scenario calculates post-disaster housing reconstruction values (e.g. repair rates and housing rebuilding permits), and a hypothetical housing recovery profile using damage assessments and building permits for rebuilding based on available investments (insurance and buy-outs). The dynamic economic resilience scenario models all potential and accelerated investments (uninsured versus insured, or buyouts for homeowners). A future dynamic economic resilience recovery scenario takes into account the benefits of housing reconstruction improvements, (e.g. levee and pump investments). The results identify an ideal sustainable long-term recovery threshold of three years after the disaster event. The results reveal the conceptualised dynamic economic resilience scenarios leads to shorter time-paths for recovery, and that the sustainable long-term recovery threshold is approximately three years after the disaster event.